Polyvinylpyrrolidone as additive for perovskite solar cells with water and isopropanol as solvents - Du, Chen; Wang, Shuo; Miao, Xu; Sun, Wenhai; Zhu, Yu; Wang, Chengyan; Ma, Ruixin (Beilstein Journal of Nanotechnology, 2019)
The recent years have witnessed a fast-paced development of perovskite solar cells (PSCs). Unfortunately, the vast majority of PSCs relies on the use of highly polar aprotic solvents during the preparation process, such as dimethylformamide (DMF), which is toxic and detrimental to both humans and the environment. Here, we describe the preparation of PSCs under ambient conditions from an aqueous solution of lead nitrate, to which polyvinylpyrrolidone (PVP) was added in order to enhance the photoelectric performance of the PSCs. By a combination of SEM, EIS, PL and UV spectroscopy and other characterization approaches, we show that the PVP additive is effective in inhibiting carrier recombination, enhancing composite resistance and reducing film defects. Ultimately, we achieved an outstanding photoelectric performance of the PVP-doped PSCs shown by a power conversion efficiency (PCE) of 15.19% and an average steady-state PCE of 14.55% under AM 1.5G simulated solar irradiation with a shadow mask of 0.1 cm2. The PCE continued to be over 80% of the initial PCE after 60 days of storage. FInally, the introduced PVP-doped PSCs present a low-cost and low-toxicity way to commercialize perovskite solar cells.
Keywords: additive; lead nitrate aqueous solution; low-toxicity process; perovskite solar cells; polyvinylpyrrolidone

(untitled) - Im, J.-H.; Lee, C.-R.; Lee, J.-W.; Park, S.-W.; Park, N.-G. (Nanoscale, 2011)

(untitled) - Jeon, N. J.; Noh, J. H.; Yang, W. S.; Kim, Y. C.; Ryu, S.; Seo, J.; Seok, S. I. (Nature, 2015)

(untitled) - Im, J.-H.; Jang, I.-H.; Pellet, N.; Grätzel, M.; Park, N.-G. (Nat. Nanotechnol., 2014)

(untitled) - Kim, H.-S.; Lee, C.-R.; Im, J.-H.; Lee, K.-B.; Moehl, T.; Marchioro, A.; Moon, S.-J.; Humphry-Baker, R.; Yum, J.-H.; Moser, J. E.; Grätzel, M.; Park, N.-G. (Sci. Rep., 2012)

(untitled) - Kojima, A.; Teshima, K.; Shirai, Y.; Miyasaka, T. (J. Am. Chem. Soc., 2009)

(untitled) - Noh, J. H.; Im, S. H.; Heo, J. H.; Mandal, T. N.; Seok, S. I. (Nano Lett., 2013)

(untitled) - Chondroudis, K.; Mitzi, D. B. (Chem. Mater., 1999)

(untitled) - Lin, Q.; Armin, A.; Lyons, D. M.; Burn, P. L.; Meredith, P. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Jiang, Q.; Zhao, Y.; Zhang, X.; Yang, X.; Chen, Y.; Chu, Z.; Ye, Q.; Li, X.; Yin, Z.; You, J. (Nat. Photonics, 2019)

(untitled) - Zhou, H.; Chen, Q.; Li, G.; Luo, S.; Song, T.-b.; Duan, H.-S.; Hong, Z.; You, J.; Liu, Y.; Yang, Y. (Science, 2014)

(untitled) - Mandujano-Ramírez, H. J.; González-Vázquez, J. P.; Oskam, G.; Dittrich, T.; Garcia-Belmonte, G.; Mora-Seró, I.; Bisquert, J.; Anta, J. A. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Liu, D.; Yang, J.; Kelly, T. L. (J. Am. Chem. Soc., 2014)

(untitled) - Malinkiewicz, O.; Yella, A.; Lee, Y. H.; Espallargas, G. M.; Graetzel, M.; Nazeeruddin, M. K.; Bolink, H. J. (Nat. Photonics, 2014)

(untitled) - Aharon, S.; Etgar, L. (Nano Lett., 2016)

(untitled) - Wu, Y.; Islam, A.; Yang, X.; Qin, C.; Liu, J.; Zhang, K.; Peng, W.; Han, L. (Energy Environ. Sci., 2014)

(untitled) - Burschka, J.; Pellet, N.; Moon, S.-J.; Humphry-Baker, R.; Gao, P.; Nazeeruddin, M. K.; Grätzel, M. (Nature, 2013)

(untitled) - Aldibaja, F. K.; Badia, L.; Mas-Marzá, E.; Sánchez, R. S.; Barea, E. M.; Mora-Sero, I. (J. Mater. Chem. A, 2015)

(untitled) - Zhang, W.; Saliba, M.; Moore, D. T.; Pathak, S. K.; Hörantner, M. T.; Stergiopoulos, T.; Stranks, S. D.; Eperon, G. E.; Alexander-Webber, J. A.; Abate, A.; Sadhanala, A.; Yao, S.; et al. (Nat. Commun., 2015)

(untitled) - Wang, F.; Yu, H.; Xu, H.; Zhao, N. (Adv. Funct. Mater., 2015)

(untitled) - Saito, J.; Oku, T.; Suzuki, A.; Akiyama, T. (AIP Conf. Proc., 2016)

(untitled) - Wang, J.-D.; Lai, M.-Y.; Chen, J.-S.; Lin, J.-M.; Chiang, J.-R.; Shiau, S.-J.; Chang, W.-S. (Arch. Environ. Health, 1991)

(untitled) - Fleming, L. E.; Shalat, S. L.; Redlich, C. A. (Scand. J. Work, Environ. Health, 1990)

(untitled) - Hsieh, T.-Y.; Wei, T.-C.; Wu, K.-L.; Ikegami, M.; Miyasaka, T. (Chem. Commun., 2015)

(untitled) - Hsieh, T.-Y.; Su, T.-S.; Ikegami, M.; Wei, T.-C.; Miyasaka, T. (Mater. Today Energy, 2018)

(untitled) - Sveinbjörnsson, K.; Kyi Thein, N. K.; Saki, Z.; Svanström, S.; Yang, W.; Cappel, U. B.; Rensmo, H.; Boschloo, G.; Aitola, K.; Johansson, E. M. J. (Sustainable Energy Fuels, 2018)

(untitled) - Li, J.; Liang, Z.; Wang, Y.; Li, H.; Tong, J.; Bao, X.; Xia, Y. (J. Mater. Chem. C, 2018)

(untitled) - Li, J.; Wang, Y.; Liang, Z.; Wang, N.; Tong, J.; Yang, C.; Bao, X.; Xia, Y. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Liang, Z.; Tong, J.; Li, H.; Wang, Y.; Wang, N.; Li, J.; Yang, C.; Xia, Y. (J. Mater. Chem. A, 2019)

(untitled) - Nie, W.; Yu, D.-G.; Branford-White, C.; Shen, X.-X.; Zhu, L.-M. (Mater. Res. Innovations, 2012)

(untitled) - Zhou, P.; Fang, Z.; Zhou, W.; Qiao, Q.; Wang, M.; Chen, T.; Yang, S. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Shim, J. W.; Cheun, H.; Meyer, J.; Fuentes-Hernandez, C.; Dindar, A.; Zhou, Y. H.; Hwang, D. K.; Kahn, A.; Kippelen, B. (Appl. Phys. Lett., 2012)

(untitled) - Ye, S.; Rao, H.; Yan, W.; Li, Y.; Sun, W.; Peng, H.; Liu, Z.; Bian, Z.; Li, Y.; Huang, C. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Sun, S.; Salim, T.; Mathews, N.; Duchamp, M.; Boothroyd, C.; Xing, G.; Sum, T. C.; Lam, Y. M. (Energy Environ. Sci., 2014)

(untitled) - Wang, S.; Ma, Z.; Liu, B.; Wu, W.; Zhu, Y.; Ma, R.; Wang, C. (Sol. RRL, 2018)

(untitled) - Wang, S.; Zhu, Y.; Sun, W.; Miao, X.; Ma, Z.; Yang, C.; Liu, B.; Li, S.; Ma, R.; Wang, C. (Sol. Energy, 2018)

(untitled) - Li, B.; Zhang, Y.; Fu, L.; Yu, T.; Zhou, S.; Zhang, L.; Yin, L. (Nat. Commun., 2018)

(untitled) - Fei, C.; Guo, L.; Li, B.; Zhang, R.; Fu, H.; Tian, J.; Cao, G. (Nano Energy, 2016)

(untitled) - Yun, J. S.; Kim, J.; Young, T.; Patterson, R. J.; Kim, D.; Seidel, J.; Lim, S.; Green, M. A.; Huang, S.; Ho-Baillie, A. (Adv. Funct. Mater., 2018)